Crickets of subfamily Nemobiinae Saussure, 1877 (Orthoptera: Grylloidea; Trigonidiidae) from China with descriptions of new genera and new species - He, Zhixin; Zhang, Tao; Ma, Libin (Zootaxa, 2021)
The article reviewed species of genera of Pteronemobius Jacobson, 1904, Speonemobius Chopard, 1924, Parapteronemobius Furukawa, 1970, Dianemobius Vickery, 1973, Polionemobius Gorochov, 1983, Giganemobius Shen & He, 2020, Qionemobius Shen & He, 2020 and proposed four new genera, Claranemobius He & Ma, gen. n., Erexitonemobius He & Ma, gen. n., Fibunemobius He & Ma, gen. n. and Impetunemobius He & Ma, gen. n., and nine new species, Claranemobius yaoquensis He & Ma, sp. n., Erexitonemobius bellus He & Ma, sp. n., Fibunemobius tamquam He & Ma, sp. n., Homonemobius amare He & Ma, sp. n., Impetunemobius brunneis He & Ma, sp. n., Polionemobius Chayuensis He & Ma, sp. n., Pteronemobius (Pteronemobius) litore He & Ma, sp. n., Pteronemobius (Pteronemobius) choui He & Ma, sp. n. and Speonemobius minor He & Ma, sp. n..